MIGRATION OF BIOMICROELEMENTS IN CLAYEY SOILS - Sotiboldiyeva Go'zalkhon Tolibjonovna; Alijonova Mehribonu Shuhrat kizi; Toshpulatova Nilufar Murodjon qizi (Web of Journals Publishing, 2025)
This article provides a theoretical analysis of the differential biogeochemical migration of biomicroelements in contaminated soils and the biosphere. It emphasizes the crucial role of biomicroelements in the exchange of substances between living and nonliving matter.
Keywords: Trace elements, biogeochemistry, biosphere, Vernadsky's concept, Matter cycle, ecological stability, human health.